REST API BACKEND APLIKASI E-COMMERCE SECONDHAND MENGGUNAKAN FRAMEWORK SPRING BOOT - Prilsafira, Tania; Kunang, Yesi Novaria; Putra, Muhammad Hatta (P3M Politeknik Negeri Banjarmasin, 2022)
The advancement in information technology is currently rapidly. Information technology can make it easier for humans to work or interact with other people. Technology applications have many various uses. One of the uses is that it can be a means of buying and selling goods or what we often call e-commerce. The SECONDHAND application developed in this study focuses on API Backend selling used goods using the Spring Boot framework. The method used is the SCRUM method which is a type of System Development Life Cycle (SDLC) design method. This research produces a REST API-based backend system.